Islamic Work Ethics and Fraud Deterrence in The Malaysian Public Sector - Norziaton Ismail Khan,; Fadzillah M.D,; Yusof Yusof,; Emmarelda M.A (Universiti Sains Islam Malaysia, 2024)
Abqari Vol. 22 (1), 2020